The Presenter in the Browser: Design and Evaluation of Human Interactive Overlays with Web Content - Maxime Cordeil; Anais Servais; Guillaume Truong; Tim Dwyer; Dhaval Vyas; Christophe Hurter (Multimodal Technologies and Interaction)
This research explores the design and evaluation of a webcam-based presentation tool that enables presenters to directly interact with web content via free-hand gestures. Our approach consists of overlaying the webcam video feed on top of web browser content to enable live presentations of any webpage. To support interactive presentations, we designed free-hand gesture interactions with the webpage to enable pointing, clicking, panning, and zooming interactions. We propose three alternatives to enable free-hand clicking: dwell time, modal key control, and a pinching interaction technique. We conducted an exploratory user study of these alternative designs to gather insights on the usability of such systems from a presenter point of view, with a focus on understanding the impact of the three techniques on flow interruptions. The results indicate that the system we propose can be used to deliver presentations effectively and that natural gestures do not disturb the flow of the presentation.